Analysis of Mangrove Suitability for Ecotourism Development Based on Geographic Information System in Kemboja Village North Kayong Regency, West Kalimantan - Nova, Nova; Raynaldo, Adityo; Saputra, Robin (Politeknik Negeri Batam, 2024)
Mangrove ecotourism has an important role in maintaining the balance of coastal ecosystems. Mangroves have various important benefits, such as in mitigating climate change with their ability to absorb carbon and protect coastal areas from abrasion. To improve tourism development, the Geographic Information System's ecotourism suitability analysis has become an important instrument. The purpose of this study is to explore mangrove types and the value of the Tourism Suitability Index. A Geographic Information System (GIS) and Tourism Suitability Index (TSI) approach was used to analyze parameter data, including mangrove density, species richness, mangrove thickness, tides and association biota. Results show that the dominant mangrove species are Xylocarpus granatum, Rhizopora mucronata, Rhizopora apiculata, and Bruguiera parviflora, with densities varying from 4 mÂ²/ind to 23 mÂ²/ind. Mangrove thickness varied from <50 to >500 meters, and biota association varied from 1 to 4 groups. The average tides vary in height, providing an important hydrological context. The land suitability analysis showed great mangrove ecotourism potential in Kemboja Village, with 2,532.20 hectares classified as highly suitable (46.07%) and 2,961.86 hectares classified as suitable (53.89%) for sustainable tourism development. Unsuitable areas cover 1.61 hectares (<1%).